Physicochemical Evaluation And Chromatographic Fingerprint Profile Of The Rind Of Ganesh Variety Of Punica Granatum Linn - J.SANGEETHA; K.VIJAYALAKSHMI (International Journal of Pharma and Bio Sciences, 2012)
Plants produce a diverse range of bioactive molecules making them a rich source of different types of medicines. Researches in bioactive substances might lead to the discovery of new compounds that could be used to formulate new and most potent antimicrobial drugs to overcome the problem of resistant to the currently available antibiotics. The main objective of the present investigations is to analyze the physiochemical characteristic of the rind of the punica granatum.